Numerische Untersuchung von Oberflächenstrukturierung zur Erhöhung der Effizienz von Kissenplatten-Wärmeübertragern - Afsahnoudeh, Reza; Holzmüller, Maik; Bader, Fabian; Homberg, Werner; Kenig, Eugeny Y.

Housing situations and local COVID-19 infection dynamics using small-area data - Freise, Diana; Schiele, Valentin; Schmitz, Hendrik (Scientific Reports)
Abstract Low socio-economic status is associated with higher SARS-CoV-2 incidences. In this paper we study whether this is a result of differences in (1) the frequency, (2) intensity, and/or (3) duration of local SARS-CoV-2 outbreaks depending on the local housing situations. So far, there is not clear evidence which of the three factors dominates. Using small-scale data from neighborhoods in the German city Essen and a flexible estimation approach which does not require prior knowledge about specific transmission characteristics of SARS-CoV-2, behavioral responses or other potential model parameters, we find evidence for the last of the three hypotheses. Outbreaks do not happen more often in less well-off areas or are more severe (in terms of the number of cases), but they last longer. This indicates that the socio-economic gradient in infection levels is at least in parts a result of a more sustained spread of infections in neighborhoods with worse housing conditions after local outbreaks and suggests that in case of an epidemic allocating scarce resources in containment measures to areas with poor housing conditions might have the greatest benefit.
Keywords: Multidisciplinary

Producing deceptive actions in sports: The costs of generating head fakes in basketball - Güldenpenning, Iris; Weigelt, Matthias; Böer, Nils Tobias; Kunde, Wilfried (Human Movement Science)
Typically, head fakes in basketball are generated to, and actually do, deteriorate performance on the side of the observer. However, potential costs at the side of the producer of a fake action have only rarely been investigated before. It is thus not clear yet if the benefit (i.e., slowed reactions in the observer) of performing a head fake is overestimated due to concurrently arising fake production costs (i.e., slowed performance in the producer of a head fake). Therefore, we studied potential head-fake production costs with two experiments. Novice participants were asked to generate passes to the left or right side, either with or without head fakes. In Experiment 1, these actions were determined by an auditory stimulus (i.e., a 440 Hz or 1200 Hz sinus or jigsaw wave). After an interstimulus interval (ISI) of either 0 ms, 800 ms, or 1500 ms, which served the preparation of the action, the cued action had to be executed. In Experiment 2, passing to the left or right, either with or without a head fake, was determined by a visual stimulus (i.e., a player with a red or blue jersey defending either the right or left side). After an ISI of either 0 ms, 400 ms, 800 ms, or 1200 ms, the cued action had to be executed. In both experiments, we observed higher reaction times (RTs) for passes with head fakes as compared to passes without head fakes for no and an intermediate preparation interval (from ISI 0 ms to 800 ms), but no difference for a long preparation interval (for an ISI of 1200 ms and 1500 ms). Both experiments show that generating fake actions produces performance costs, however, these costs can be overcome by a longer preparation phase before movement execution.
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

The Third Knowledge Dimension: From a Binary System to a Three-limbed Epistemology - Hagengruber, Ruth (Women Philosophers on Economics, Technology, Environment, and Gender History)
The thesis of this paper is that a new kind of epistemology evolves from the use of artificial intelligence. The path it takes changes our understanding of the world, of human values and also of science and will be irreversible. The question that arises is whether this form of intelligence also influences our knowledge structure. By this I mean the area that we outline philosophically as the epistemological area. So the question is, under these circumstances, is the way we gain knowledge today still comparable to the definitions that philosophy has provided us with for centuries? The answer is: No! The paper sketches in broad outlines what the cornerstones of change will be and what consequences this will have for our way of understanding.

Women Philosophers on Economics, Technology, Environment, and Gender History
In times of current crisis, the voices of women are needed more than ever. The accumulation of war and environmental catastrophes teaches us that exploitation of people and nature through violent appropriation and enrichment for the sake of short-term self-interest exacts its price. This book presents contributions on the currently most relevant and most urgent issues: reshaping the economy, environmental problems, technology and the re-reading of history from the non-western and western tradition. With an outlook into the problems of class, race and gender in its intersectional framing, the collection offers a unique overview of current research in these fields and contributes to the renewal and contemporary presentation of feminist thought from partly concrete perspectives with regard to factual issues.

Women Philosophers on Economics, Technology, Environment and Gender History. Shaping the Future – Rethinking the Past. - Hagengruber, Ruth Edith (Women Philosophers on Economics, Technology, Environment, and Gender History)

Das Aufbegehren der Eroberten. Absichten, Formen und Deutungen im europäischen Mittelalter (8. bis 14. Jahrhundert) - Kamp, Hermann (Eroberte im Mittelalter. Umbruchssituationen erleben, bewältigen, gestalten)

Minimizing Eye Movements and Distractions in Head-Mounted Augmented Reality through Eye-Gaze Adaptiveness - Wecker, Daniel; Yigitbas, Enes (Proceedings of the ACM Symposium on Spatial User Interaction (SUI 2023))

GaMoVR: Gamification-Based UML Learning Environment in Virtual Reality - Yigitbas, Enes; Schmidt, Maximilian; Bucchiarone, Antonio; Gottschalk, Sebastian; Engels, Gregor (Science of Computer Programming)

Transitional Cross Reality Interfaces for Spatially Demanding Search and Collect Tasks - Schmidt, Leonard; Yigitbas, Enes (Proceedings of the 27th International Workshop on Personalization and Recommendation)

ABIS 2023 – 27th International Workshop on Personalization and Recommendation - Neumayr, Thomas; Yigitbas, Enes; Augstein, Mirjam; Herder, Eelco (Proceedings of the Mensch & Computer (2023))

Comparison of Required Competences and Task Material in Modeling Education - Soyka, Chantal; Ullrich, Meike; Striewe, Michael; Schaper, Niclas (Enterprise Modelling and Information Systems Architectures)
The reform of the European academic landscape with the introduction of bachelor's and master's degree programs has brought about several profound changes for teaching and assessment in higher education. With regard to the examination system, the shift towards output-oriented teaching is still one of the most significant challenges. Assessments have to be integrated into the teaching and learning arrangements and consistently aligned towards the intended learning outcomes. In particular, assessments should provide valid evidence that learners have acquired competences that are relevant for a specific domain. However, it seems that this didactic goal has not yet been fully achieved in modeling education in computer science. The aim of this study is to investigate whether typical task material used in exercises and exams in modeling education at selected German universities covers relevant competences required for graphical modeling. For this purpose, typical tasks in the field of modeling are first identified by means of a content-analytical procedure. Subsequently, it is determined which competence facets relevant for graphical modeling are addressed by the task types. By contrasting a competence model for modeling with the competences addressed by the tasks, a gap was identified between the required competences and the task material analyzed. In particular, the gap analysis shows the neglect of transversal competence facets as well as those related to the analysis and evaluation of models. The result of this paper is a classification of task types for modeling education and a specification of the competence facets addressed by these tasks. Recommendations for developing and assessing student's competences comprehensively are given.
Keywords: conceptual modeling; higher education; competence-oriented assessment; task analysis; graphical modeling

Die Doppelwirkung von Information für klimafreundliches Handeln - Frick, Marc; Foese, Dario; Von Graevenitz, Kathrine; Kesternich, Martin; Wagner, Ulrich
Informationen sind für eine erfolgreiche Klimapolitik in doppelter Hinsicht wichtig: Sie werden benötigt, wenn Potenziale zur Vermeidung von Emissionen identifiziert und klimapolitische Instrumente ausgewählt werden. Und sie sind zentral, damit Bürger/innen selbst Entscheidungen im Sinne des Klimaschutzes treffen können.
Keywords: General Medicine

Implementing Digital Responsibility through Information Systems Research: A Delphi Study of Objectives, Activities, and Challenges in IS Research - Beverungen, Daniel; zur Heiden, Philipp; Lehrer, Christiane; Trier, Matthias; Bartelheimer, Christian; Bradt, Tobias; Distel, Bettina; Drews, Paul; Ehmke, Jan Fabian; Fill, Hans-Georg; Flath, Christoph M.; Fridgen, Gilbert; et al.

Methodical Approach to Reducing Design Time by using Neural Networks in Early Stages of Concept Development - Ott, Manuel; Meihöfener, Niclas; Mozgova, Iryna (Proceedings of the 34rd Annual International Solid Freeform Fabrication Symposium 2023)
Modern companies often face various challenges in concept development of products or systems. Design engineers prepare initial concepts as 3D models. These are then simulated by computational engineers. If requirements are not met, this necessitates an iterative process that runs between the design and computation departments until a valid concept is created. Design methods such as topology optimization are often used here. The upcoming result is then attempted to be adapted to certain manufacturing processes. These iteration loops can sometimes take a very long time, since the model construction and structural optimization generate large computational efforts. The present work shows on an example a methodical approach, which represents a first proof of concept, to solving this problem, including a description of methods and techniques, as well as possible problems in a detailed analysis concerning training data for neural networks and their abstraction capabilities. It is evident that additional research work needs to be conducted for further utilization in order to address all arising questions.

Aushandlungen von Inklusion und Exklusion im Kontext der (nicht-)Verfügbarkeit mobiler Medien. Ein rekonstruktiver Blick auf die Mediatisierung berufsschulischer Möglichkeitsräume. - Dehmel, Lukas; Meister, Dorothee (Jahrbuch Medienpädagogik 20. Inklusive Medienbildung in einer mediatisierten Welt. Medienpädagogische Perspektiven auf ein interprofessionelles Forschungsfeld.)

Quasi-In Situ Localized Corrosion of an Additively Manufactured FeCo Alloy in 5 Wt Pct NaCl Solution - Pramanik, Sudipta; Krüger, Jan Tobias; Schaper, Mirko; Hoyer, Kay-Peter (Metallurgical and Materials Transactions A)
Abstract FeCo alloys are important materials used in pumps and motors in the offshore oil and gas drilling industry. These alloys are subjected to marine environments with a high NaCl concentration, therefore, corrosion and catastrophic failure are anticipated. So, the surface dissolution of additively manufactured FeCo samples is investigated in a quasi- in situ manner, in particular, the pitting corrosion in 5.0 wt pct NaCl solution. The local dissolution of the same sample region is monitored after 24, 72, and 168 hours. Here, the formation of rectangular and circular pits of ultra-fine dimensions (less than 0.5 µ m) is observed with increasing immersion time. In addition, the formation of a corrosion-inhibiting surface layer is detected on the sample surface. Surface dissolution leads to a change in the surface structure, however, no change in grain shape or grain size is noticed. The surface topography after local dissolution is correlated to the grain orientation. Quasi- in situ analysis shows the preferential dissolution of high-angle grain boundaries (HAGBs) leading to a change in the fraction of HAGBs and low-angle grain boundaries fraction (LAGBs). For the FeCo sample, a potentiodynamic polarisation test reveals a corrosion potential (E corr ) of − 0.475 V referred to the standard hydrogen electrode (SHE) and a corrosion exchange current density (i corr ) of 0.0848 A/m 2 . Furthermore, quasi- in situ experiments showed that grains oriented along certain crystallographic directions are corroding more compared to other grains leading to a significant decrease in the local surface height. Grains with a plane normal close to the $$\langle {1}00\rangle$$ ⟨ 100 ⟩ direction reveal lower surface dissolution and higher corrosion resistance, whereas planes normal close to the $$\langle {11}0\rangle$$ ⟨ 110 ⟩ direction and the $$\langle {111}\rangle$$ ⟨ 111 ⟩ direction exhibit a higher surface dissolution.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

Schulpraktikum zwischen Kind und Nebenjob? Einfluss von sozialen und organisationalen Bedingungsfaktoren auf das Belastungserleben Lehramtsstudierender im Praxissemester - Vogelsang, Christoph; Brandhorst, André (Herausforderung Lehrer* Innenbildung-Zeitschrift Zur Konzeption, Gestaltung Und Diskussion)
Trotz der Annahme, dass Langzeitpraktika im Lehramts-studium hohe Belastungen für Studierende darstellen können, sind empirische Analysen zum Einfluss sozialer (z.B. die Betreuung eigener Kinder, Pflegeaufgaben) und organisationaler Bedingungsfaktoren (z.B. Erwerbstätigkeit, Fahrzeiten zur Praktikumsschule, Zusatzkosten) rar. Daher wurden in diesem Beitrag im Rahmen einer Sekundäranalyse evaluativer Daten Zusammenhänge zwischen dem Belastungserleben von N = 611 Lehramtsstudierenden im Praxissemester an der Universität Paderborn und verschiedenen Bedingungsfaktoren untersucht. Das Belastungserleben wurde vor und nach dem Praxissemester mit Hilfe des Maslach-Burnout-Inventars (MBI-SS) erfasst. Regressionsanalysen ergaben, dass soziale und organisationale Bedingungsfaktoren kaum Unterschiede im Belastungserleben aufklären. Als einzige bedeutende Faktoren mit kleinen Effekten erwiesen sich die Fahrzeit zur Praktikumsschule und die Höhe evtl. zusätzlicher Materialkosten. Auch durch Clusteranalysen ermittelte Gruppen von hochbelasteten Studierenden zeichnen sich nicht durch spezifische soziale oder organisationale Bedingungsfaktoren aus.
Keywords: Praxissemester; Belastung; Burnout; Lehramtsstudium; soziale Situation

The Origination of Online Reviews in B2B Markets: A Qualitative Study on the Underlying Motives of Review Writers - Seutter, Janina

Frontal theta reveals further information about neural valence‐dependent processing of augmented feedback in extensive motor practice - A secondary analysis - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (European Journal of Neuroscience)
Abstract Supplementing an earlier analysis of event‐related potentials in extensive motor learning (Margraf et al., 2022a, 2022b), frontal theta‐band activity (4–8 Hz) was scrutinized. Thirty‐seven participants learned a sequential arm movement with 192 trials in each of five practice sessions. Feedback, based on a performance adaptive bandwidth, was given after every trial. Electroencephalogram (EEG) was recorded in the first and last practice sessions. The degree of motor automatization was tested under dual‐task conditions in a pre‐test–post‐test design. Quantitative error information was transported in both feedback conditions (positive and negative). Frontal theta activity was discussed as a general signal that cognitive control is needed and, therefore, was expected to be higher after negative feedback. Extensive motor practice promotes automatization, and therefore, decreased frontal theta activity was expected in the later practice. Further, it was expected that frontal theta was predictive for subsequent behavioural adaptations and the amount of motor automatization. As the results show, induced frontal theta power was higher after negative feedback and decreased after five sessions of practice. Moreover, induced theta activity was predictive for error correction and, therefore, an indicator of whether the recruited cognitive resources successfully induced behavioural adaptations. It remains to be solved why these effects, which fit well with the theoretical assumptions, were only revealed by the induced part of frontal theta activity. Further, the amount of theta activity during practice was not predictive for the degree of motor automatization. It seems that there might be a dissociation between attentional resources associated with feedback processing and attentional resources associated with motor control.
Keywords: General Neuroscience